Security Access Local Wireless Network with Use of Free Tools - Ballesteros, Juan (2016)
In this paper we present an audit IEEE 802.11x networks to check how secure these networks are for use in the home and office, will be used for this purpose free software Linux with aircrack suite, tests were done for the 2 encryptions WEP and WPA these popular encryptions for security in wireless networks, also show different forms to develop attacks for example denial of service sniffers, fake authentication, etc. The dictionary attack is the most popular and will be the starting point for the audit, but it is important also to mention other equally effective methods to develop this attack.